Contact and gustatory effects of spinosad on the survivability of Sitophilus oryzae L. (Coleoptera: Curculionidae) in wheat - Habiba, Umme; Islam, W; Parween, Selina (Bangladesh Journal of Zoology, 2019)
The present study was planned to evaluate the effect of spinosad on the survivability and development of Sitophilus oryzae on four wheat varieties viz., BARI-26, BARI-28, Shatabdi-21 and Prodip-24. Three doses in three replications for spinosad were applied to four wheat varieties. Spinosad concentrations significantly increased the total developmental period compared to the control in a dose-dependent manner on four wheat varieties. The highest developmental period took 41.67 ± 0.33 days to become adult was recorded in S-21 at 0.0003 μl/g of spinosad in F1. All adults of F1 did not reach in F2 because surprisingly all adults died after emergence. So, no developmental period was found in S-21 (0.00±0.00) and B-28 (0.00 ± 0.00) days at 0.0003 μl/g spinosad in F2. On the other hand, five mated females were released on the treated wheat with different concentrations of spinosad for 10 - 15 days; then they were removed. Treated wheat was checked for up to 30 to 60 days and observed the progeny for two successive generations (1st and 2nd). Each combination of insect species, insecticide rate, and exposure duration were replicated three times. Among four wheat varieties, the lowest adult emergence was recorded as 08.00 ± 0.58 in F1 and totally controlled in F2 generation in S-21 variety at 0.0003 μl/g. Spinosad concentrations significantly increased the total developmental period compared to the control in a dosedependent manner on four wheat varieties. Bangladesh J. Zool. 47(2): 253-262, 2019